Pengaruh Pesan Iklan Tokopedia Edisi "Ciptakan Peluangmu" terhadap Minat Berbisnis Online pada Remaja di Masa Pendemi di Kota Makassar - Musyarrif Ali; Andriansyah Andriansyah (Journal of Communication Sciences (JCoS), 2023)
The aim of this research is to determine whether the advertising message of Tokopedia, with the theme "Ciptakan Peluangmu" influences business interest among teenagers during the pandemic in the city of Makassar. The research method used is quantitative research, with a population of 338,444 teenagers aged 18-29 in Makassar. The sample size used is 100 individuals. The primary data collection technique involves using a questionnaire through the Google Forms platform, while secondary data is obtained through observation and documentation. The data analysis technique used in this research is simple linear regression analysis, conducted using the SPSS version 25 software. The results of this research indicate that the advertising message has a significant influence on business interest among teenagers during the pandemic in Makassar. With a calculated t-value of 7.473 > the tabled t-value of 1.671, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. This means that there is an influence of the advertising message of Tokopedia, with the theme "Ciptakan Peluangmu" on business interest among teenagers during the pandemic in Makassar, with a significance level of 0.000 < 0.05. Based on the coefficient of determination, which indicates the magnitude of the influence of the advertising message on teenagers in Makassar, it is found to be 0.491 or 49.1%. This means that 49.1% of the business interest among teenagers in Makassar during the pandemic can be attributed to the advertising message. The remaining 50.9% is influenced by other factors.